Loss of Cdx2 Expression in Primary Tumors and Lymph Node Metastases is Specific for Mismatch Repair-Deficiency in Colorectal Cancer - Dawson, Heather; Koelzer, Viktor H.; Lukesh, Anne; Mallaev, Makhmudbek; Inderbitzin, Daniel; Lugli, Alessandro; Zlobec, Inti (Frontiers in Oncology, 2013)
Background: Approximately 20% of all colorectal cancers are hypothesized to arise from the “serrated pathway” characterized by mutation in BRAF, high-level CpG Island Methylator Phenotype, and microsatellite instability/mismatch repair (MMR)-deficiency. MMR-deficient cancers show frequent losses of Cdx2, a homeodomain transcription factor. Here, we determine the predictive value of Cdx2 expression for MMR-deficiency and investigate changes in expression between primary cancers and matched lymph node metastases. Methods: Immunohistochemistry for Cdx2, Mlh1, Msh2, Msh6, and Pms2 was performed on whole tissue sections from 201 patients with primary colorectal cancer and 59 cases of matched lymph node metastases. Receiver operating characteristic curve analysis and Area under the Curve (AUC) were investigated; association of Cdx2 with clinicopathological features and patient survival was carried out. Results: Loss of Cdx2 expression was associated with higher tumor grade (p = 0.0002), advanced pT (p = 0.0166), and perineural invasion (p = 0.0228). Cdx2 loss was an unfavorable prognostic factor in univariate (p = 0.0145) and multivariate [p = 0.0427; HR (95% CI): 0.58 (0.34–0.98)] analysis. The accuracy (AUC) for discriminating MMR-proficient and – deficient cancers was 87% [OR (95% CI): 0.96 (0.95–0.98); p < 0.0001]. Specificity and negative predictive value for MMR-deficiency was 99.1 and 96.3%. One hundred and seventy-four patients had MMR-proficient cancers, of which 60 (34.5%) showed Cdx2 loss. Cdx2 loss in metastases was related to MMR-deficiency (p < 0.0001). There was no difference in expression between primary tumors and matched metastases. Conclusion: Loss of Cdx2 is a sensitive and specific predictor of MMR-deficiency, but is not limited to these tumors, suggesting that events “upstream” of the development of microsatellite instability may impact Cdx2 expression.